2020
DOI: 10.1002/alz.12179
|View full text |Cite
|
Sign up to set email alerts
|

Retinal imaging in Alzheimer's and neurodegenerative diseases

Abstract: In the last 20 years, research focused on developing retinal imaging as a source of potential biomarkers for Alzheimer's disease and other neurodegenerative diseases, has increased significantly. The Alzheimer's Association and the Alzheimer's & Dementia: Diagnosis, Assessment, Disease Monitoring editorial team (companion journal to Alzheimer's & Dementia) convened an interdisciplinary discussion in 2019 to identify a path to expedite the development of retinal biomarkers capable of identifying This is an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 70 publications
3
114
0
1
Order By: Relevance
“…The retina is an essential part of the CNS. Due to its transparent nature to light, it is possible to use less invasive and high-resolution imaging modalities to visualise the retina [26,27]. It is predominantly known for its involvement in converting light energy into electrical signals [28].…”
Section: Retinal Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…The retina is an essential part of the CNS. Due to its transparent nature to light, it is possible to use less invasive and high-resolution imaging modalities to visualise the retina [26,27]. It is predominantly known for its involvement in converting light energy into electrical signals [28].…”
Section: Retinal Microgliamentioning
confidence: 99%
“…Frequently occurring symptoms of MS involves the ocular pathway such as RNFL thinning, optic neuritis (ON) characterised by inflammatory damage to the optic nerve and uveitis characterised by intraocular inflammation of the vitreous body, retina, and uveal tract [62][63][64][65][66]. It has also been reported that such retinal changes may occur before changes in the rest of the CNS in many neurodegenerative diseases, including MS [26]. These recent findings have led to much interest in retinal research.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Yet, imaging of the skull-shielded brain poses various limitations for widespread screening in the clinical setting. The retina is a central nervous system organ that exhibits many of the pathological hallmarks of AD (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and is far more accessible for repeated and highresolution imaging (32)(33)(34)(35)(36)(37)(38)(39)(40). Dysfunctional pericytes in the blood-brain barrier (BBB) are signi cant contributors to the pathogenesis of vascular cognitive impairment, including cerebral small vessel and large vessel disease and AD (26, 41).…”
Section: Introductionmentioning
confidence: 99%
“…However, the strong link between the eye and the central nervous system is supported by evidence that the ocular alterations existing in various neurodegenerative pathologies of the CNS and visual manifestations sometimes precede central symptoms. Moreover, the retina is a CNS compartment that can be easily analyzed with optical techniques, such as, for example, the optical coherence tomography (OCT), so retinal changes may reflect the pathological features in the brain early in the disease processes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%